Tinjauan Yuridis Mengenai Aturan Hukum Pemutusan Hubungan Kerja terhadap Dosen Perguruan Tinggi Swasta - Albi Mahardian; Achmad Rifqi Nizam; Achmad Rizky Hasani; Muhammad Fadhil (Faculty of Law Hang Tuah University, 2019)
The research was to analyze and understand the provisions of labor law that apply to private university lecturers affected by termination of employment the rule of law for the lecturers who work in private universities specifically regarding two things, firstly, the rule of law that applies to lecturers working in private tertiary institutions and second, what rights can be obtained by private tertiary lecturers who experience termination of employment. This research was prepared using the normative juridical research method with a statute and conceptual approach. Based on the results of research that can be concluded from higher education institutions in act 13/2003 can be interpreted as companies and managers of private education that can be interpreted as entrepreneurs, so that the working relationship of private university lecturers is a legal relationship that is subject to labor law, and if there is a dispute between lecturers with private universities, the rule of law used is act 2/2004 because lecturers working in private universities are private workers and private universities are entrepreneurs.